Scheduling resumable simple linear deteriorating jobs on a single machine with an availability constraint to minimize makespan - Ji, Min; Cheng, T.C.E. (Computers & industrial engineering, 2010)
We consider a single-machine scheduling problem in which the processing time of each job is a simple linear deteriorating function of its waiting time. The machine is subject to an availability constraint. Jobs interrupted by machine unavailability can resume their processing. The objective is to minimize the makespan. We first show that the problem can be solved optimally by 0–1 integer programming. We then prove that the problem is NP-hard in the ordinary sense and there exists a fully polynomial time approximation scheme for it.